Política fundiária no Brasil : trajetória e desafios jurídicos - Scaloppe, Roberta Sales Tertuliano (2018)
This paper aims to elucidate the trajectory of land policy in Brazil and to point out some of the juridical challenges posed to its attainment in the present time. In order to do so, it was analyzed the linkage of the Democratic State of Right to the guidelines drawn up in constitutional seat, as well as its role in guaranteeing and concretizing fundamental social rights. Since public policies is the most appropriate way for state action, the aim was to delimit a legal concept of public policies, in order to follow the land policy in this modality. The terminology and content distinction was made between agrarian, agricultural, land and agrarian reform policies. It was investigated the legal framework that underpinned state action in agrarian matters, as well as the socioeconomic and political conjuncture in force in the main moments of normative and constitutional transition occurred in Brazil, from the beginning of colonization until the advent of the Federal Constitution of 1988. Between the contemporary juridical challenges, it was pointed out the normative framework that conditions the action of the state agents and state institutions in the process of formulation and execution of the public policies, imposing to the land policy the duty to realize social justice. We investigated the doctrinal positions favorable and contrary to agrarian reform, focusing on their relevance in the current stage of development of Brazilian society. The concept of agri-environmental public policies was discussed, as well as the need for land policy to fit this modality, encompassing a socio-environmental bias. As a kind of agrienvironmental public policy, the promotion of family farming as a viable alternative for achieving sustainability in rural areas was highlighted. Finally, it was verified that the normative apparatus made available to the public authorities to provide the necessary substrate for the development of a public policy capable of realizing fundamental social rights in rural areas, democratizing access to land and ensuring the observance of agrarian sustainability, identified with the social function of rural property, in its triple dimension - economic, social and ecological.